2021
DOI: 10.1002/joa3.12653
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid convergent ablation versus endocardial catheter ablation for atrial fibrillation: A systematic review and meta‐analysis

Abstract: Introduction Endocardial catheter ablation (ECA) for atrial fibrillation (AF) has limited efficacy. Hybrid convergent procedure (HCP) with both epicardial and endocardial ablation is a novel strategy for AF treatment. In this meta‐analysis, we aimed to evaluate the efficacy and safety of HCP in AF ablation. Method We performed a comprehensive literature search for studies that evaluated the efficacy and safety of HCP compared with ECA for AF. The primary outcome was fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…found no difference between the hybrid procedure and epicardial ablation in the prevention of arrhythmia recurrence, while the hybrid procedure was associated with higher complication rates. Mhanna et al 28 . found significantly higher rates of complications in their meta‐analysis of eight studies (797 AF patients).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…found no difference between the hybrid procedure and epicardial ablation in the prevention of arrhythmia recurrence, while the hybrid procedure was associated with higher complication rates. Mhanna et al 28 . found significantly higher rates of complications in their meta‐analysis of eight studies (797 AF patients).…”
Section: Discussionmentioning
confidence: 96%
“…Five meta-analysis articles explored the effectiveness and safety of hybrid ablation for AF. [26][27][28][29][30] The number of prospective controlled studies on nonparoxysmal AF was too small, and these five metaanalysis studies included more single-arm studies or retrospective analysis studies for analysis, and their conclusions were also different.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the effectiveness of HCA may be underestimated in these studies. Lastly, previous meta-analyses included studies with a variety of surgical techniques (subxiphoid/ unilateral or bilateral thoracoscopic/mini-thoracotomy/sternotomy), which vary in terms of their efficacy and risk profile [ 9 , 18 , 20 , 22 ]. The resultant heterogeneity in these meta-analyses was significant [ 8 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The resultant heterogeneity in these meta-analyses was significant [ 8 , 22 ]. Mhanna et al reported a heterogeneity of 77% in their primary outcome (freedom from AF at last follow-up), and Zhang et al reported a heterogeneity of 86% in the same outcome [ 9 , 18 ]. A strength of the present study was the inclusion of RCT’s and PSM studies only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation